Synthesis of 2-Cycloalkyl-4-chlorophenols - Ashaduzzaman, Md.; Saha, Dipti; Saha, Manoranjan (Dhaka University Journal of Science, 2012)
2-Cycloalkyl-4-chlorophenols were synthesized in high yield by the alkylation of p-chlorophenol with cyclopentanol and cyclohexanol in the presence of perchloric acid as catalyst. The effects of the variation of temperature, molar ratio of p-chlorophenol to cycloalcohols, time of reaction and amount of catalyst on the reactions were also studied. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11504 Dhaka Univ. J. Sci. 60(2): 199-202, 2012 (July)